The 'More Capable Peer': Approaches to Collaborative Learning in a Mixed-Ability Classroom. Issue 1 (2nd January 2016) - Roberts, Jenny
Abstract: This essay challenges assumptions that those labelled as 'high achievers' are in some way 'held back' by those perceived as having lower initial capability. By exploring collaborative pedagogical approaches and focussing on my experiences with two students, with widely differing initial capabilities, and exploring how they have influenced each other's learning, I argue that organisational models that separate students based on perceived ability can be damaging. Allowing time and space for students to collaborate on a range of tasks and creating a classroom atmosphere which values the contributions of all can enable those students deemed of lower ability to become useful learning tools for their 'more capable peers' as well as vice versa. Against those versions of the Vygotskian zone of proximal development that privilege the role of the 'more capable peer', I argue that collaborative forms of learning can be mutually beneficial.